ANALISIS PRA-KOMERSIALISASI PANEL GREENING MATERIAL MENGGUNAKAN LUMUT - , Titisari J ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The global warming phenomenon enforced most of the stakeholders, not only academicians but also industries, to find out the solutions of its effects around them. One of the mitigation eforts to tackle these effects is making greening material. Greening material is a plant which is attached on the building to reduce the impacts of environmental destruction. The material which is used in this research is moss (Sphagnum sp.). This research is a gradually research which is divided into some main topics. For research conducted by this time, it focused on assesing the readiness of this panel to be commercialized. The objectives of this research was pursuing pre-commercialized analysis of Greening Material panel using Sphagnum moss that was divided into technical analysis, financial analysis, marketing analysis, and business strategy analysis. We used 3 types of respondents,as they were environmental stakeholders (government board and non-governmental organization), real estate developer (business), and the society of Merapi disaster prone area. The society itself was devoted on the people who were practicing restaurants business. Some methods were used in this research like focus group discussion, in-depth interview, and survey by questionnaires. The conclusion of this research was the product is feasible by technical assesment. It could be produced by the applied technology. Financially, this product is feasible by the calculation of Break Even Point (BEP), payback period, internal rate of return (IRR), cash-flow, and also R/C ratio with some assumptions. The market price of this panel was IDR 90.652 with 15% of profit margin. From the marketing assessment, we accepted that people were interested in this product because it was very innovative. In addition, they still can not get the reliability or robustness of this product, so that we need to prove it to them. Respondents assumed that the price is still too high. For the final step, we used SWOT analysis diagram and Canvas Business Model to evaluate and make the business plan in the future.